The Relationship between Energy Consumption and Economic Growth: Evidence from Different Income Country Groups - Yasar, Nermin (International Journal of Energy Economics and Policy, 2017)
This study analyses the relationship between energy consumption and economic growth for 119 countries during the period of 1970-2015, classified into four groups regarding to the World Bank income ranking. The main motivation of this study is to analyze whether the causal relationship differs between different income groups of countries. For this purpose, panel ARDL boundary approach and Granger causality test were used. The results of the study indicate that the causal relationship between energy use and economic growth differs depending on which income group country belongs to. We conclude that the feedback hypothesis is supported for upper-middle income group in the long run and high-income group, while conservation hypothesis is supported for upper-middle income group in the short run and lower-middle income group in the long run. Finally, neutrality hypothesis is supported for low and lower middle-income groups in the short run. Keywords: Energy consumption, economic growth, panel unit root, ARDL boundary approach, panel causality JEL Classifications: Q44, Q48, O4